PENGARUH MACAM ZPT DAN LAMA PERENDAMAN TERHADAP PERTUMBUHAN AWAL BIBIT SENGON (Albizia falcataria) VARIETAS SENGON LAUT - Illa Novia Anggraini; Yushi Mardiana (Universitas Islam Kadiri, 2017)
Sengon is chosen for planting because it has many advantages and provides benefits. Growing Regulatory Substance (ZPT) is an organic compound used to stimulate root growth, shoot growth, germination process, etc. The purpose of this research is to know the effect of ZPT and the duration of immersion on early growth of Sengon seeds and their interaction. The research was conducted in DesaToyoresmi, Kec. Ngasem, Kab. Kediri uses rice field with sandy loam soil texture from February to April 2017. Based on the research, it can be concluded that: 1) synthetic ZPT treatment has significant effect on germination percentage, plant height, number of leaves, root number, dry weight, wet weight, but no significant effect on stem diameter, root length, greenish leaves and leaf area; 2) the immersion treatment had significant effect on the percentage of germination on treatment of P2 (immersuin 2 hours) and P3 (immersion 3 hours), but no significant effect on other observation variables; 3) interaction between synthesized ZPT treatment and time of plotting to germination percentage with highest treatment on J3P3, but no interaction between synthetic ZPT and long immersion to other observation variables.